Analysis of the aerodynamic characteristics of an ejection seat system using computational fluid dynamics - Rahman, Md. Mahbubur; Prakash, Ved; Chandel, Sunil; Thakur, D. G.; Čep, Robert; Khedkar, Nitin; Salunkhe, Sachin; Abouel Nasr, Emad S. (Frontiers in Mechanical Engineering, 2023)
In the present work, the investigation of the aerodynamic characteristics of an ejection seat occupant is carried out using the commercially available Computational Fluid Dynamics (CFD) software ANSYS-Fluent. 3-D Reynolds-averaged Navier-Stokes equations are solved to get the aerodynamic coefficients of the ejection seat system. For this analysis, an unstructured grid of an ejection seat occupant is generated using ANSYS meshing. Validation and the performance of three different turbulence models have been analyzed at Mach number 0.6. Based on the suitable turbulence model further analysis of the aerodynamic coefficient of the ejection seat occupant is calculated at Mach numbers 0.35, 0.45, 0.55, 0.65, and 0.75. For all the Mach numbers the angle of attack is varied from -15 0 to 15 0 with an increment of 5 0 and the yaw angle is changed from 0 0 to 60 0 with an increment of 10 0 . From the results, it is observed that the magnitude of the axial force decreases with the increasing angle of attack and yaw angle. Similarly, the normal force coefficient and pitching moment coefficient decrease with the increase of the angle of attack. The side force coefficient, yawing moment, and rolling moment coefficient increase with the increase of the yaw angle.